An efficient energy-saving scheme incorporating dozing and sleep modes for CLS-based WDM-PONs with colorless ONUs - Zhong, Wende (2013)
We propose and demonstrate an efficient energy-saving scheme incorporating dozing and sleep modes for WDM-PONs with centralized light sources (CLS). The novel scheme is based on simple power detection and local transmission request. Two logic control units are designed to switch the operation modes of the respective ONUs and their associated transceivers in the OLT. The scheme feasibility is experimentally verified with 10Gbit/s downstream and 1.25Gbit/s upstream transmissions. The simulation results reveal that the energy-saving of the ONUs in the online state mainly arises from the dozing mode, not from the sleep mode, while the energy-saving of the associated transceivers in the OLT is contributed mainly from the situation where ONUs are in the offline state.